FAKTOR – FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING PADA PEMERINTAH KABUPATEN ENDE - Maria Goreti Goo, Katharina; JMV. Mulyadi; Syam, M. Ardiansyah (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
The purpose of this study was to analyze the Competence of Human Resources, the Government's Internal Control System, the Role of Internal Audit, the Utilization of IT, Compliance with Regulations / Regulations and Implementation of SAP with organizational commitment as a moderating variable to the Quality of Financial Reports in the Ende District Government. The population of this study is the financial report compilers who have the duties and responsibilities in preparing financial statements in the Work Units in the Ende Regency Government totaling 32 Regional Devices (OPD). Data collection by distributing 128 questionnaires to financial report compilers. The sampling technique uses a census method in which the entire study population is used as the research sample. The method of data analysis uses moderation regression analysis (MRA). The results of this study prove that Competence of Human Resources, Utilization of IT, Compliance with Regulations / Regulations and Implementation of SAP has a significant effect on the quality of financial statements while the Government Internal Control System and Internal Audit Roles have no significant effect on the Quality of Financial Statements. Organizational Commitment as a moderating variable can moderate the influence of the Government's Internal Control System, the Role of Internal Audit and SAP Implementation. on the Quality of Financial Statements, but Organizational Commitment cannot moderate the effect of Competence of Human Resources on the Use of Information Technology and Compliance with Regulations / Regulations on the Quality of Financial Statements.